Molecular subtypes predict the preferential site of distant metastasis in advanced breast cancer: a nationwide retrospective study - Fan, Jin-Hu; Zhang, Su; Yang, Huan; Yi, Zong-Bi; Ouyang, Qu-Chang; Yan, Min; Wang, Xiao-Jia; Hu, Xi-Chun; Jiang, Ze-Fei; Huang, Tao; Tong, Zhong-Sheng; Wang, Shu-Sen; et al. (Frontiers in Oncology, 2023)
Objective This study aimed to explore possible associations between molecular subtypes and site of distant metastasis in advanced breast cancer (ABC). Methods 3577 ABC patients were selected from 21 hospitals of seven geographic regions in China from 2012-2014. A questionnaire was designed to collect medical information regarding demographic characteristics, risk factors, molecular subtype, recurrence/metastasis information, and disease-free survival (DFS). The cancers were classified into Luminal A, Luminal B, HER2-enriched and Triple Negative subtypes. Chi-square test and multivariate Cox proportional hazard models were performed to explore the associations between molecular subtypes and distant metastasis sites. Results A total of 2393 cases with molecular subtypes information were finally examined. Patients with Luminal A (51.1%) and Luminal B (44.7%) were most prone to bone metastasis, whereas liver metastasis was more frequently observed in HER2-enriched ABC patients (29.1%).The cumulative recurrence and metastasis rates of ABC patients at 36 months of DFS were the most significant within molecular types, of which Triple Negative was the highest (82.7%), while that of Luminal A was the lowest (58.4%). In the adjusted Cox regression analysis, Luminal B, HER2-enriched and Triple Negative subtypes increased the risk of visceral metastasis by 23%, 46% and 87% respectively. In addition, Triple Negative patients had a higher probability of brain metastasis (HR 3.07, 95% CI: 1.04-9.07). Conclusion Molecular subtypes can predict the preferential sites of distant metastasis, emphasizing that these associations were of great help in choices for surveillance, developing appropriate screening and cancer management strategies for follow-up and personalized therapy in ABC patients.